Resting heart rate as an index for monitoring physiological condition during high altitude training in cross-country skiers - Takeda, M.; Kato, H.; Mimura, T.; Shimamoto, H.; Endoh, H.; Radak, Z. (Sciene and nordic skiing III, 2016)
In high altitude training, it is important to increase the training volume gradually for first week after finishing acute adaptation to high altitude to avoid overtraining and deterioration of physical condition. Therefore, it is reasonable to have an index for monitoring physical condition and acclimatization status in high altitude training. However, we have not had suitable index to monitor physical condition of athletes during high altitude training. It has been suggested that autonomic nervous system (ANS) changes in high altitude compared to sea level (Hainswirth et al., 2007; Iwasaki et al., 2006; Kanai et al., 2001). It controls heart rate (HR) and constriction and expansion of blood vessels and this function of ANS affects to the physical condition and performance in high altitude. Kanai et al. (2001) have reported that activity of ANS decreased with sojourn at 2,700 m and 3,700 m and the component of low frequency (LF) of R-R interval in electrocardiogram (ECG) of heart rate variability (HRV) which reflects sympathetic nervous tone increased and high frequency (HF) of R-R interval which reflects parasympathetic tone decreased. Iwasaki et al. (2006) have reported sympathetic nervous activity significantly increased in the inspired air of 15 % of oxygen as compared to 21 % with no significant change in parasympathetic activity. These findings suggested that ANS tried to adapt to high altitude condition. In this study, we have evaluated physiological meanings of resting HR and HRV as an index for monitoring the physiological condition and acclimatization status during 2 weeks of high altitude training in cross-country skiers. (Original introduction)